Emerging research and issues in behavioral disabilities - Landrum, Timothy J.; Cook, Bryan G.; Tankersley, Melody (Advances in learning and behavioral disabilities ;, 2018)
The challenges associated with the education and treatment of children and youth with emotional and behavioral disorders (EBD) have proven to be both persistent and exceedingly complex. Thus, our best hope for improving outcomes for students with or at risk for EBD lies not in miracle cures or the eradication of all disorders, but in the incremental progress that furthers our understanding of the nature of EBD, enabling us to systematically refine interventions. Toward these goals, this volumefocuses on emerging research and issues related to students identified with or at risk of EBD.Chapters within the volume include reports of original research, and summaries of new and emerging research issues. Specific topics include: bullying; technology-based self-monitoring; issues around the direct observation of both student and teacher behavior; the characteristics of youth served in residential or other alternative settings because of their EBD; and the application of function-based logic to social skills intervention. Two additional chapters examine issues around identifying evidence-based practice in EBD, including guidance for practitioners who may be overwhelmed by the challenges of teaching students with EBD, as well as the vast array of resources they must sift through to locate credible and reliable information on effective interventions.